2003
DOI: 10.1046/j.1365-2133.2003.05338.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin analogue scintigraphy in Merkel cell tumours

Abstract: These data confirm that scintigraphy with the radiolabelled somatostatin analogue octreotide is not clinically helpful in detecting metastases from Merkel cell carcinoma. In this relatively small sample the method generated false-positive or false-negative results in five of 11 cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 20 publications
1
29
0
2
Order By: Relevance
“…The potential use of SRI in MCC staging remains controversial. Most studies involving 111 indium-octreotide scintigraphy [17,19,20,21] found this technique to be less sensitive than current imaging by CT scan or 18 F-fluorodeoxyglucose PET. In the largest series evaluating 20 patients with MCC, 111 indium-octreotide scintigraphy demonstrated a sensitivity of 78 and a specificity of 95%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The potential use of SRI in MCC staging remains controversial. Most studies involving 111 indium-octreotide scintigraphy [17,19,20,21] found this technique to be less sensitive than current imaging by CT scan or 18 F-fluorodeoxyglucose PET. In the largest series evaluating 20 patients with MCC, 111 indium-octreotide scintigraphy demonstrated a sensitivity of 78 and a specificity of 95%.…”
Section: Discussionmentioning
confidence: 99%
“…Papotti et al [29] reported SSTR2A transcripts in 9 out of 10 MCCs using RT-PCR, including 5 cases (50%) with high levels of SSTR2A transcripts, which is consistent with the expression of SSTR2A protein in 59.2% of tumours in our study. Durani et al [19] reported SSTR2A expression in all 5 MCC cases investigated using immunohistochemistry; however, the characteristics and validity of their antibody were unclear, and no controls were described. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IMP3 is normally expressed in early embryonic tissues, and may also be expressed in a proportion of nonsmall cell lung carcinomas and pancreatic adenocarcinomas. Further, K homology domain-containing proteins may be overexpressed in high-grade neuroendocrine lung carcinomas and extrapulmonary small cell carcinomas [62][63].…”
Section: Discussionmentioning
confidence: 99%